EXAMINE THE ROLE OF GENDER IN THE PRODUCTION AND CONSUMPTION OF FUJIAN YONGCHUN PAPER WEAVING PAINTING, INVESTIGATING HOW GENDER NORMS, DIVISION OF LABOR, AND CULTURAL PERCEPTIONS SHAPE ARTISTIC PRACTICE, APPRENTICESHIP, AND PARTICIPATION IN RELATED CULTURAL ACTIVITIES - Jiang, Han; Nattapong Prompongsaton; Pat Kotchapakdee (Fonseca, Journal of Communication, 2025)
This paper aims to analyze the process and forms of gender relations in painting the traditional craft of paper weaving in Yongchun, Fujian Province with the focus on the position of men and women in the framework of culture and economic conditions of this region. Employing 59 semi-structured interviews, 571 participant observations, and two survey questions, this gendered qualitative and quantitative study examines how males and females manage manufacture artistry and financial results when working in a traditional family lineage and a contemporary mechanical production line. From the revelations made, it is clear that women solely perform the tasks involved in the cutting and weaving processes, while men take the upper hand when it comes to painting and designing. This division is enshrouded in the cultural and historical milieu of a particular region and reinforces patriarchal culture in particular regions. A brief socio-economic assessment demonstrates the discrepancies of income between genders thereby establishing the general lenient approach towards the role of women in this craft. Nevertheless, there are several key points the study notices, and the first one is education Attracting more women to higher skilled jobs and Education – Being the best way of dismantling traditional barriers. Furthermore, concepts of female gods revered in cultural themes are encouraging when analyzed with the local realism faced by women, therefore there appears to be a trend between the cultural paradigm and gender politics. This paper also advocates for reconsidering some signs of the past and offers possible ways to change the status quo by pointers on education and social, and political instruments, as well as by altering the attitude towards women’s contributions to the arts. Not only does the study provide insights into the gender reformation in traditional craftworks but it also brings a comprehensive solution for breaking the barriers of gender inequality in Cultural Industries.